Pure Void Space and Fracture Pore Space in Fault-Fractured Zones - Li, Xiaogang; Xu, Guoqiang; Wu, Chen; Yin, An; Wu, Shihu; Zuza, Andrew V.; Chen, Gang; Li, Zhiwu; Xu, Shaohua; Li, Yiwen (Frontiers in Earth Science, 2021)
Fault-fractured pore space is complex and difficult to predict and evaluate. For a single independent ramp-flat fault-bend fold structure, the pure void space between two fault walls equals the integrated fracture pore spaces within the fault damage zone if it were concentrated on the fault plane. Using an area balancing technique and geometrical relationship, we have developed a two-dimensional (2D) model to calculate the pore space of fractures associated with fault development. The development and distribution of fault detachment voids or fault fracture pore space are controlled by the physical properties of the deforming medium, mechanics of deformation, and geometry of a fault-ramp structure. We demonstrate how concordant or discordant folding of the fault wall rock affects the nature of fault-fracture pore space. The pure void space and fracture pores in the fault zone can be quantitatively described by the following parameters: initial ramp angle and height, overlap ramp length, throw and slipping displacement, stack thickness, curvature and derivation of the angle between bed and fault plane (Rθ), and dip isogons. Rθ reflects the conformity of two opposite fault sections and the folding accordance of two walls, and it is a key element for the development and distribution of fracture pore space in a fault zone. Furthermore, we observed natural outcrops supporting and validating our model assumptions in the foreland fault system, Central China.